THE RAILWAY TO THE PACIFIC OCEAN (FOR THE 100-TH ANNIVERSARY OF THE TRANS-SIBERIAN RAILWAY) - V. Persianov; A. Kurbatova; E. Kurbatova (Вестник университета)
The article gives a short description of the history of construction of the Trans-Siberian Railway. It covers the situation on Russia’s railways in the second half of the 19th century and debatable questions related to the selection of railway alignment, its function and financing of construction. The article also contains the information about work progress, its scale and construction costs.